(3GdMHd GdhKjb aj fUQI GdUOjbs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3abO hbY Edi SDGd ai bhdg JYGdi (B(((3dG jUdgG EdG GdCTbi GdPi cPH hJhdi hSjLfHgG GdCJbi GdPi jDJi eGdg jJRci(B)) (3Edi BNQ GdShQI s
(3BNQgG (B:s
(3dG GdBjGJ hdG GdcdeGJ s
(3Vef eLehY , JQJjHgG (B: 50s
(3YdjgG hba ddLGeY GdCYXe GdecJHI GdCMeOjI HJhfS HJGQjN (B1256 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B629s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJGQjNs